Adolescent nonsuicidal self-injury and cortisol response to the retrieval of adversity: A sibling study. (December 2019) - Reichl, Corinna; Brunner, Romuald; Bender, Nina; Parzer, Peter; Koenig, Julian; Resch, Franz; Kaess, Michael
Highlights: Siblings had moderate agreements regarding experiences of childhood adversity (CA). Adolescents with nonsuicidal self-injury (NSSI) reported more CA than siblings. Adolescents with NSSI showed a decrease in cortisol during the retrieval of CA. Severity of CA was not related to the slope of cortisol during the retrieval of CA. Adolescents with NSSI had increased hair cortisol levels compared to siblings. Abstract: Background: There is evidence for alterations in hypothalamus-pituitary-adrenal (HPA) axis response to the retrieval of traumatic events among individuals with Posttraumatic Stress Disorder. However, no study has so far investigated HPA response to trauma retrieval among individuals engaging in non-suicidal self-injury (NSSI). In the present study, we compared reports of childhood adversity (CA) between adolescents engaging in NSSI and their siblings and tested for differences in the cortisol response to the retrieval of CA. Methods: The sample consisted of 32 adolescents engaging in NSSI (Mage = 15.8 years) and their siblings (Mage = 15.6 years). Standardized interviews were used for the assessment of CA, NSSI, and axis I diagnoses. Salivary cortisol was measured before and after the trauma interview. Basal HPA axis activity was measured in hair. Results: Reports of CA were moderately interrelated between siblings. Adolescents engaging in NSSI reported more severe CA. A significant decrease of salivary cortisol during the trauma interview was found only in the NSSI group. The NSSI group had significantly higher hair cortisol levels. Conclusions: Moderate relations in siblings' reports of CA point to non-shared experiences that may play a role in the development of NSSI. In the NSSI group, the decrease of salivary cortisol during the interview may be explained by a downregulation of the HPA axis subsequent to the retrieval of former experience of CA.